Pengaruh pra-perlakuan osmotik dalam pengeringan terhadap karakteristik buah kering: meta analisis - Tri Yulni; Waqif Agusta; Mohammad Nafila Alfa; Astuti Astuti; Tantry Eko Putri Mariastuty; Herdiarti Destika Hermansyah; Lusiana Kresnawati Hartono; Primawati Yenni Fauziah; Dian Anggraeni; Meivie Meiske Jetty Lintang (AGROINTEK, 2024)
Osmotic pretreatment is commonly used in drying to preserve the quality of dried fruit. Several studies have been conducted to evaluate the impact of osmotic pretreatment on the quality of dried food, but, these evaluations have mainly been qualitative and have relied heavily on the author's. A meta-analysis was performed in this work to investigate the osmotic pretreatment effect on the properties of dried fruit, such as water activity, moisture content, crispness, and hardness. The Scopus database yielded 2832 potential references, of which 13 met the criteria for meta-analysis. Subgroup analysis on the type of fruit, osmotic agent, concentration, drying method, and temperature was performed to ascertain the influence of moderator variables on the evaluated fruit's characteristics. The data collection and statistical analysis were both done with the OpenMEE software. According to the findings, osmotic pretreatment significantly affected the product's water activity, moisture content, and crispness. Still, it had no such impact on the hardness of the product. In the analysis subgroup, all types of fruit, solution concentration, drying method, and temperature increased water activity, decreased water content, and improved crispness. Meanwhile, it was determined that each fruit's hardness varied depending on the type of fruit, solution concentration, drying method, and temperature. Except for xylitol, all osmotic agents increased water activity. Sucrose and stachyose affect moisture content and hardness differently. Sucrose can enhance crispness. Although osmotic pretreatment improved the characteristics of dried fruit (moisture content and crispness), it negatively influenced water activity, as was concluded. The moderator variable influences the characteristics of dried fruit.